The effect of rapid automatized naming on foreign language anxiety among dyslexic students - Abdelaziz Abdelfattah Elfeky; Abdulhamid Fathi Alholah; Afaf Saeed Al-Budaiwi; Radwa Hassan Yacoub; Ashraf Ragab Ibrahim; Mohamed Ali Nemt-allah (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study examined whether rapid automatized naming (RAN) training—a cognitive intervention focused on improving the speed and accuracy of naming visual stimuli—could effectively reduce foreign language anxiety (FLA) among dyslexic learners. Using a single-group pretest-posttest design with follow-up assessment, a 10-week RAN training intervention was implemented with 30 dyslexic students (18 males, 12 females; aged 13-14 years) from Egyptian preparatory institutes. The intervention consisted of individual 30-minute sessions conducted 3 times per week, systematically progressing from basic single-category naming tasks to complex mixed-category combinations designed to enhance processing fluency and automaticity. Using the foreign language classroom anxiety scale (FLCAS), anxiety levels were measured before intervention, immediately after, and at 8-week follow-up. Results revealed significant reductions in overall FLA (partial η²=.32), with particularly notable improvements in communication apprehension (partial η²=.33) and anxiety in the English classroom (partial η²=.29). Test anxiety showed initial improvement but returned to near-baseline levels at follow-up, while fear of negative evaluation remained largely unchanged. Results suggest that RAN training may be associated with reductions in FLA among dyslexic students, though causal relationships cannot be established without a control group.